NIKAH HIBAH DALAM PERSPEKTIF TAFSIR AYAT AHKAM - Birbik, M. Hafil (International Conference on Humanity Education and Society (ICHES), 2023)
Marriage is a contract that legitimizes the relationship between a man and a woman with the purpose of building a family that is sakinah (tranquil), mawaddah (loving), and rahmah (merciful). In its implementation, there are specific pillars and conditions that must be fulfilled, including the use of specific utterances in the ijab (offer) and qabul (acceptance). While the majority of Islamic jurists stipulate the use of the terms zawaj (marriage) and nikah (matrimony), some Hanafi scholars permit the use of the term hibah (gift). This article examines the arguments employed by Hanafi scholars, as well as the counter-arguments from the majority of jurists who assert that the permissibility of using the term hibah was a specific privilege granted exclusively to Prophet Muhammad (SAW). This study aims to clarify the legal status of using the hibah utterance in the marriage contract based on the interpretation of legal verses (tafsir ayat al-ahkam) and the opinions of Islamic jurists.